Decremental response in patients with amyotrophic lateral sclerosis during repetitive nerve stimulation and its relationships with impaired homeostasis - Jinghong Zhang; Yang Li; Qiang Shi (Frontiers in Aging Neuroscience)
BackgroundPrevious studies have suggested that neuromuscular junction (NMJ) denervation plays a critical role in amyotrophic lateral sclerosis (ALS). Repetitive nerve stimulation (RNS) has been used as a technique to test neuromuscular transmission, but the sensitivity and stability of its parameters have not been investigated in patients with ALS. In addition, the impact of impaired homeostasis on NMJ stability in patients with ALS remains unclear.MethodsA total of 421 patients with ALS were enrolled. Data on their clinical, biochemical and electrophysiological indicators were divided into a training set (collected from June 2019 to June 2022) and a test set (collected from July 2022 to June 2023). The coefficient of variation (CV) was used to assess the extent of variability. Stepwise regression was used in independent variable selection and model building.ResultsIn patients with ALS, area decrement had a higher rate of abnormal result and a lower CV than amplitude decrement. No significant difference in the rate of abnormal decrement was found when the first compound muscle action potential (CMAP) was compared with either the fourth or fifth one. Moreover, multivariate regression analysis suggests high-density lipoprotein cholesterol (HDL-C) had the greatest impact on decremental response, followed by serum uric acid (UA) and forced vital capacity (FVC). Females had a larger range of area decrement than males.ConclusionDuring RNS test, assessing area decrement significantly enhances our ability to detect the impairment of neuromuscular transmission in patients with ALS. Independent factors contributing to decremental response need to be considered in drug development and clinical trials targeting NMJ in patients with ALS.